Conservation and use of native tropical fruit species biodiversity in Asia: Proceedings of the first annual meeting of Tropical Fruit Genetic Resources Project, 6-9 February 2001, Pattaya, Thailand - Mal, B.; Ramamani, Y.S.; Ramanatha Rao, V.; International Plant Genetic Resources Institute (2001)
These proceedings deal with the deliberations of the first annual meeting of the project organized by IPGRI-APO at Pattaya, Thailand from 6-9 February 2001. The objectives of this meeting were to review the progress and outputs of different activities in the collaborating countries, enhance collaboration with regional and international organizations, provide a platform to country coordinators to mutually interact and update their information, and to develop annual work plans. These activities and concerns were well covered in four technical sessions. The proceedings include highlights of the meeting and a follow-up action, and nine papers on PGR activities on tropical fruits covering status of diversity, collection and conservation strategies, germplasm exchange and use, information and documentation, and network activities on tropical fruits (FAO, UTFANET, TFNet) and prospects of CIRAD's collaboration.